2010
DOI: 10.1007/s10620-010-1431-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Reflux Esophago-Laryngitis Model in Rats

Abstract: Our modified chronic acid reflux esophagitis model proved useful in establishing a rat reflux esophago-laryngitis model, with both pathological laryngeal findings and reflux esophagitis shown to be improved by administration of a proton pump inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Inhalation anesthesia was performed with isoflurane. After laparotomy, duodenal stenosis was created by wrapping the duodenum near the pylorus with a 2.5 mm-wide piece of 18-Fr Nelaton catheter (diameter, 4.0 mm; Terumo, Tokyo, Japan) as described previously [20]. Then, to prevent dislodgment, the catheter was immobilized by suturing it to the serosa of the gastric antrum with 4-0 silk thread.…”
Section: Induction Of Chronic Acid Reflux Esophagitis In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhalation anesthesia was performed with isoflurane. After laparotomy, duodenal stenosis was created by wrapping the duodenum near the pylorus with a 2.5 mm-wide piece of 18-Fr Nelaton catheter (diameter, 4.0 mm; Terumo, Tokyo, Japan) as described previously [20]. Then, to prevent dislodgment, the catheter was immobilized by suturing it to the serosa of the gastric antrum with 4-0 silk thread.…”
Section: Induction Of Chronic Acid Reflux Esophagitis In Ratsmentioning
confidence: 99%
“…Regarding the administration route and dose of rabeprazole, Tanaka et al [21] reported that subcutaneous injection of RPZ at doses of 0.3-10.0 mg/kg/day to rats was effective for reducing gastric ulcers. We previously reported that these doses were appropriate for this rat esophagitis model [20]. Therefore, we selected a low dose (1.0 mg/kg/day) and a sufficient dose (10.0 mg/kg/day) of RPZ against rat esophagitis in the present study.…”
Section: Induction Of Chronic Acid Reflux Esophagitis In Ratsmentioning
confidence: 99%
“…(1,4,12,25). Only two models were designed to study an untraumatized larynx in mildly sedated adult rabbits or nonsedated adult rats (2,18). In contrast, our model was designed to closely reproduce clinical conditions, by posterior laryngopharyngeal instillations of a gastric juice surrogate (pepsin ϩ HCl) in nonsedated newborn lambs.…”
Section: Our Ovine Neonatal Model Of Simulated Rlmentioning
confidence: 99%
“…Laryngopharyngeal reflux (LPR), a variant of gastroesophageal reflux disease (GERD), contributes to inflammation of upper aerodigestive mucosa in ways similar to the pathophysiological process measured in lower esophagus with GERD. [1][2][3] Although prior studies have explored the link between acid and pepsin in laryngeal inflammatory and neoplastic disease, [4][5][6] chronic effects of gastroduodenal fluids have not been mechanistically regarded a risk factor in laryngopharyngeal inflammatory disease or cancer. 3,[7][8][9][10][11][12][13] Rather, the precise role of gastroduodenal reflux in laryngopharyngeal carcinogenesis and its etiopathological mechanisms remains unclear.…”
Section: Introductionmentioning
confidence: 99%